THE AMBIGUITY OF MYSTICISM - Höllhuber, Ivo (HUMANITAS DIGITAL, 2021)
To what extreme degree "popular science adopted ham conceptions of mysticism and offered at times quite a caricature of its most typical representatives appears obvious when consulting one of the most renowned encyclopaedias.